Evaluation of the finnish diabetes risk score (FINDRISC) for diabetes screening in Kayseri, Turkey - Atayoğlu, Ali Timuçin; İnanç, Neriman; Başmısırlı, Eda; Çapar, Aslı Gizem (Elsevier Science Ltd, 2020)
Aim: Diabetes is a major health problem worldwide, as its prevalence is increasing dramatically. Lifestyle modification can delay or prevent the onset of type 2 diabetes. Therefore, screening for prediabetes and type 2 diabetes risk through an assessment of risk factors is important. The objective of the study was to investigate the risk for type 2 diabetes using the Finnish Diabetes Risk Score (FINDRISC) in Kayseri.Methods: In total, 1500 adults aged 18 years or older were interviewed using the FINDRISC as Diabetes Risk Questionnaire and fasting serum glucose levels. The findings of FINDRISC were grouped according to gender and a score of 15 and above was accepted as a high risk in terms of Type 2 diabetes.Results: 13.5% of the participants were in the high- risk group. There was a statistically significant relationship between total FINDRISC score and gender (p < 0.001). While 15.2% of the women were in the high -risk group, 12.4% of the men were in the high- risk group. The percentage of women in the low-risk group (35.9%) is less than the men with low- risk of diabetes (38.5%). As the BMI increased, the individuals were found to have a high risk evaluated with the use of FINDRISC. 14.3% of women with waist circumference >88 and 6.7% of men with waist circumference >102 were in the high- risk group. (p < 0.001)Conclusions: Risk of diabetes was found to be higher with the FINDRISC score as the BMI and waist circumference increased. FINDRISC can be used in the primary care for this purpose; fast and easy to be applied.
Keywords: Diabetes; FINDRISC; Prediabetes; Prevention; Primary Care